Construcción de memorias a través de herramientas de comunicación participativa: el caso de la Ruta Pacífica de las Mujeres. Sección regional Valle del Cauca (2018)
This community internship had the purpose of generating tools of participative communication as an initiative to create memories of the feminist movement Ruta Pacífica de las Mujeres: Valle del Cauca. Social movement of political action with national character, which works for the negotiation of the armed conflict in Colombia through dialogue; seeking to make visible the effects that the war had on the life and body of women. Given its history, the movement brings together activists who are community leaders and, to a large extent, women survivors of the internal armed conflict. Hence the need to develop a proposal that would lead to the creation of memories of the feminist movement; understanding memory as a collective construction of meanings, which is formed due to the daily and significant actions that take place in the context of the Ruta Pacífica and contribute to the durability of the movement over time. Therefore, the community internship was developed based on qualitative methodology Participative Action Research . In this sense, through direct work with the women of the Ruta Pacífica, media training workshops were implemented to proceed with the collective construction of participative communication tools. Which resulted in the creation of audiovisual, radio, written and photographic products; to account for the record of the experiences of the social movement; during the period July-November of the year 2017. These activities enabled the collection of historical data, life stories and information on the processes of social transformation that are carried out by the women of the movement. In this way, it is worth noting that the Ruta Pacífica Valle appropriated its knowledge and experiences; and they used communication as an instrument of visualization and construction of collective memory